(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
While cultural diversity describes the individual and social differences of people who differ in terms of gender, race, age, socio-economic status, and of course cultural and geographic origin, inclusion is the interaction between people despite this diversity. , describes the need to establish communication, in today’s global environment composed of diverse people, it is precisely this cultural diversity and inclusivity that needs to be taken into account in the creation of advertising texts, which are the basis of marketing. Although cultural diversity and inclusion have recently become hot topics in many fields of research, European countries have paid special attention to these elements in the world of advertising. This article examines how cultural diversity and inclusiveness are reflected in advertising texts and how urgent this initiative is.